2006
DOI: 10.1002/ijc.22341
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant promoter methylation of insulin‐like growth factor binding protein‐3 gene in human cancers

Abstract: Insulin-like growth factor binding protein-3 (IGFBP-3) is postulated to be a mediator of growth suppression signals. Here, we examined the methylation status of IGFBP-3 to correlate to clinicopathological factors in human cancers. The methylation status of IGFBP-3 was determined by bisulfite DNA sequencing and was correlated with expression semi-quantified by real-time RT-PCR to develop a methylation-specific PCR (MSP) assay for IGFBP-3. Using the MSP assay, we examined the methylation status of IGFBP-3 in gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 42 publications
4
63
0
1
Order By: Relevance
“…Both of these genes inhibit activation of the Wnt-signaling pathway by preventing the binding of Wnt ligands to the frizzled transmembrane receptors. The frequency of WIF-1 methylation in mesothelioma tissues was similar to that reported in previous studies (13,15,29) and its frequency is higher in mesothelioma compared to that of other genes, such as p16 (11.4%), RASSF1A (20.2%) and IGFBP-3 (32%) (8,9,20). This result suggests that WIF-1 methylation might play an important role in mesothelioma.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Both of these genes inhibit activation of the Wnt-signaling pathway by preventing the binding of Wnt ligands to the frizzled transmembrane receptors. The frequency of WIF-1 methylation in mesothelioma tissues was similar to that reported in previous studies (13,15,29) and its frequency is higher in mesothelioma compared to that of other genes, such as p16 (11.4%), RASSF1A (20.2%) and IGFBP-3 (32%) (8,9,20). This result suggests that WIF-1 methylation might play an important role in mesothelioma.…”
Section: Discussionsupporting
confidence: 88%
“…RASSF1A, ESR1, IGFBP3, APC, CCND2, HPPBP1, BMP3b and BMP6 have been reported to be down-regulated by promoter methylation in mesothelioma. It has been suggested that these types of epigenetic changes contribute to tumorigenesis in mesothelioma (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Characteristics of HOPX-b promoter methylation as compared with those of other genes associated with a high frequency of promoter methylation CDH4 (95%) (Miotto et al, 2004), Integrina4 (85%) (Park et al, 2004), KLF4 (80%) (Wei et al, 2005), Reprimo (79%) (Takahashi et al, 2005), Runx3 (45-71%) (Waki et al, 2003;Oshimo et al, 2004a), PGP9.5 (50-73%) (Yamashita et al, 2006;Tokumaru et al, 2008), RIZ1 (37-69%) (Tokumaru et al, 2003;Oshimo et al, 2004b), XAF1 (69%) (Zou et al, 2006), IGFBP3 (67%) (Tomii et al, 2007) and NMDAR2B (61%) (Liu et al, 2007) were the top 10 genes reported to have the highest frequencies of methylation in gastric cancer. We examined whether the frequency of HOPX-b methylation was comparable with those reported for such genes and whether HOPX-b methylation was a cancer-specific event in nine gastric cancer cell lines and the preliminary data set of 10 matched pairs (Supplementary Table 1) by bisulfite sequencing analysis (Figure 1b and Supplementary Figure 1).…”
Section: Hopx-b Promoter Structurementioning
confidence: 99%
“…IGFBP-3 has anti-proliferative, as well as, pro-apoptotic effects and suppression of IGFBP-3 has been implicated in the progression of several other tumors. 27 Also decreased were levels of transcripts for vascular endothelial growth factor (VEGF) receptor-1 (FLT1 or VEGFR1) (Ϫ22.7-fold), which interacts with VEGF-A, -B, and-E, as well as placental growth factor. Of relevance, low levels of VEGFR1 have been found in infantile hemangioma caused by mutations in the genes encoding VEGFR2 and TEM8.…”
Section: Endothelial-pericyte Signaling Systems In Proliferating Hemamentioning
confidence: 99%